Antibacterial Activity of N-Hexane and Ethyl Acetate Fractions Of Pandanus Nut (P. Julianettii) Against Oral Pathogens - Nur, Wardah Rafidah; Naid, Tadjuddin; Herwin, Herwin (Journal Microbiology Science, 2025)
Oral infections caused by Streptococcus mutans and Porphyromonas gingivalis are common health problems. This in vitro study aimed to evaluate the antibacterial activity of Pandanus nut (Pandanus julianettii) with n-hexane and ethyl acetate fractions against these pathogens through agar diffusion assays. The n-hexane and ethyl acetate fractions were subjected to agar diffusion testing, with Minimum Inhibitory Concentration (MIC) values determined at 0.8% and 0.2% respectively against both bacterial strains. Subsequent Minimum Bactericidal Concentration (MBC) testing revealed values of 6.4-12.8% for n-hexane fraction and 3.2-6.4% for ethyl acetate fraction. In agar diffusion assays, the n-hexane fraction at 12.8% concentration produced inhibition zones of 15.54±0,20 mm on S. mutans and 15.46±0,35 mm on P. gingivalis. The ethyl acetate fraction showed significantly larger inhibition zones of 18.76±0,79 mm against S. mutans and 15.59±0,42 mm against P. gingivalis at the same concentration. These findings demonstrate that both n-hexane and ethyl acetate fractions of Pandanus nut possess substantial antibacterial activity against oral pathogens.